Numerical simulation of dispersion and nonlinear characteristics of microstructured silica fibres with a thin suspended core in a wide range of their parameters - Anashkina, E. A.; Andrianov, A. V.; Leuchs, Gerd (Quantum Electronics, 2020)
Dispersion and nonlinear characteristics of microstructured silica fibres with a thin suspended core surrounded by three, four or six air holes have been studied theoretically in the wavelength range 1 - 2 μm. It has been shown that, owing to strong fundamental mode confinement near the core, the Kerr nonlinearity coefficient can exceed the nonlinearity coefficient of standard telecom fibre SMF28e by two orders of magnitude. The large waveguide contribution allows for effective group velocity dispersion management. Estimates are presented that demonstrate the feasibility of using suspended core fibre exhibiting Kerr nonlinearity for generating non-classical light: a state with squeezed quantum fluctuations in one of the quadrature components of a cw laser signal at a wavelength near 1.55 μm.
CRIS-Team Scopus Importer:2023-04-20